Handgrip and knee extension strength as predictors of cancer mortality: A systematic review and meta-analysis (2018)
The specific role of different strength measures on mortality risk needs to be clarified to gain a better understanding of the clinical importance of different muscle groups, as well as to inform intervention protocols in relation to reducing early mortality. The aim of the systematic review and meta-analysis was to determine the relationship between muscular strength and risk of cancer mortality. Eligible cohort studies were those that examined the association between muscular strength, as assessed using validated tests, and cancer mortality in healthy youth and adults. The hazard ratio (HR) estimates obtained were pooled using random effects meta-analysis models. The outcome was cancer mortality assessed using the HR (Cox proportional hazards model). Eleven prospective studies with 1 309 413 participants were included, and 9787 cancer-specific deaths were reported. Overall, greater handgrip (HR = 0.97, 95% CI, 0.92-1.02; P =.055; I2 = 18.9%) and knee extension strength (HR = 0.98, 95% CI, 0.95-1.00; P =.051; I2 = 60.6%) were barely significant associated with reduced risk of cancer mortality. Our study suggests that higher level of muscular strength is not statistically associated with lower risk of cancer mortality. © 2018 John Wiley and Sons A/S. Published by John Wiley and Sons Ltd